Applications of airborne lidar for the assessment of animal species diversity. Issue 8 (5th July 2014) - Simonson, William D.; Allen, Harriet D.; Coomes, David A.; Tatem, Andrew
Summary Habitat structure is important in explaining species diversity patterns for many animal groups. If we could map habitat structure over large spatial scales, we could use habitat structure–species diversity (HS–SD) relationships to model species diversity and inform conservation planning and management. Traditional approaches for measuring habitat structure cannot be applied over entire landscapes, but remote sensing tools are now able to overcome this limitation. Here, we explore the potential of airborne lidar for the assessment and monitoring of animal species diversity in terrestrial environments. We review the habitat attributes commonly recorded in the study of HS–SD relationships and the spatial scale of their measurement, in papers published between 1960 and 2013. We also gather evidence for the use of lidar to make relevant measurements at similar scales. Eight out of 15 attributes of habitat structure commonly used in published studies relate to the vertical dimension of habitat. The core strength of lidar is that it is a vertical profiler, and this technology can be used to derive estimates of all but one of these structural attributes. Lidar can also be used to improve the measurement of the four commonly used attributes focusing on the horizontal heterogeneity of habitat patches. The spatial grain and extent of HS–SD studies is usually within the operational capability of airborne lidar; when a vertical measure of habitat structure has been employed, this is true in 84% of published studies. The potential efficacy of lidar in this field of biodiversity studies is underlined by several published examples of lidar modelling of animal species diversity. We conclude that lidar remote sensing is fit for the purpose of biodiversity assessment and monitoring through its ability to characterize habitat structure, a key driver of animal species diversity, over large spatial scales. We advocate wider application of lidar‐based HS–SD indicators to help tackle the current biodiversity crisis. In combination with other remote sensing products, these indicators may support the implementation and monitoring of environmental legislation, inform gap analyses and the planning of management actions for protected areas and species, and drive greater synergy with forest‐based climate change mitigation.